Connecting supply, short-sellers and stock returns: Research challenges - Reed, Adam V. (Journal of Accounting and Economics, 2015)
One key challenge for the short selling literature is to identify the incremental contribution of various measures of short sale constraints. Although variables such as loan fee, loan supply and short interest are determined simultaneously in the market for borrowing stock, new incremental information may be found in each variable examined. Papers such as Beneish et al. (2015) attempt to disentangle the effect of one particular variable, and attempt to shed light on the parallel challenge faced by investors in determining which variables will make the most impact on returns as well as trading costs. We discuss a number of practical approaches to this challenge, and we also consider a potentially new take that considers accounting-data-driven anomalies as one of the possible exogenously determined variables in the equilibrium of the equity loan market.